2009
DOI: 10.3140/bull.geosci.1113
|View full text |Cite
|
Sign up to set email alerts
|

Early Middle Frasnian platform reef strata in the Moravian Karst interpreted as recording the atmospheric dust changes: the key to understanding perturbations in the punctata conodont zone

Abstract: Development of new stratigraphic techniques has led to better understanding of the compositional variability and quantity of dust-related impurity components in pure marine limestones, with a considerable impact on stratigraphic resolution and explanation of causality. The early Middle Frasnian (E-MF, punctata Zone) stratigraphic interval was selected for this study in order to assess the contribution of atmospheric dust and to distinguish between the robust climatically driven anomalies and the potential dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…These interpretations come from the general assumption that there is a relationship between the amount of terrigeneous supply responsible for increased MS values and eustasy (Ellwood et al 2000). However, there are also various factors which play against this generalization (e.g., Hladil et al 2006Hladil et al , 2009Da Silva et al 2009;Vacek et al 2010). The MS signal may be strongly modified by secondary processes such as magnetite neomorphism during diagenesis or secondary remagnetization (see e.g., Riquier et al 2010), which certainly devalues interpretations that the primary MS record reflects depositional conditions and processes.…”
Section: Interpretation and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These interpretations come from the general assumption that there is a relationship between the amount of terrigeneous supply responsible for increased MS values and eustasy (Ellwood et al 2000). However, there are also various factors which play against this generalization (e.g., Hladil et al 2006Hladil et al , 2009Da Silva et al 2009;Vacek et al 2010). The MS signal may be strongly modified by secondary processes such as magnetite neomorphism during diagenesis or secondary remagnetization (see e.g., Riquier et al 2010), which certainly devalues interpretations that the primary MS record reflects depositional conditions and processes.…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…In the Czech Republic this approach has been used mainly in the Devonian of the Prague Synclinorium (central Bohemia; e.g., Slavík et al 2000;Crick et al 1997Crick et al , 2001Ellwood et al 2006;Hladil et al 2010b;Koptíková 2010;Koptíková et al 2010a, b;Vacek 2010;Vacek et al 2010) and Moravosilezian Zone (Moravia; e.g., Hladil 2002;Hladil et al 2000Hladil et al , 2003aHladil et al , b, 2006Hladil et al , 2009Geršl & Hladil 2004;Bábek et al 2007;Boulvain et al 2010). Physical stratigraphic methods have been used for intrabasinal or interregional correlations as well as auxiliary data for characteristics of depositional environments and their evolution, especially in cooperation with sedimentologists and biostratigraphers.…”
mentioning
confidence: 99%
“…A cross-reference is hereby given to the "out-of-balance" facies rich in microbial ("bacinellid") crusts and other structures assumed to be coeval to the Early Aptian OAE 1a (e.g., IMMENHAUSER et al, 2005;RAM-EIL et al, 2010). Also the increased abundance of Devonian thaumatoporallecean-like forms corresponds to dysoxic episodes and events, e.g., in the Upper Givetian, basal Frasnian or with the Middle Frasnian, e.g., in the Pa. punctata Zone (HLADIL et al, 2009). It is very likely that both the major and medium-magnitude Palaeozoic events which caused pro-liferation of microbially dominated benthic communities and organomineralization of sediment in the post-crisis period (BOURQUE et al, 2004) led to the right setting for production and release of the cysts.…”
Section: Plate VIImentioning
confidence: 99%
“…A positive correlation between MS and independent palaeo-environmental proxies is the first indication that the primary signal is preserved. These non-magnetic palaeo-environmental proxies include the following: † Clay or quartz content or insoluble residues in carbonate rocks are typically of detrital origin and are classical parameters to be compared with MS in order to infer a primary, detrital origin of the MS signal (Ellwood et al 1999;English 1999;Hladil et al 2009). For example, showed that the MS increased with increasing quartz content on two Middle Devonian sections from Belgium (Fig.…”
Section: Comparison With Other Proxiesmentioning
confidence: 99%